(untitled) (REVISTA NODO, 2019)
This article originates from one of the ffieldwork projects carried out during my academic studies for the master’s degree in Restoration of Architectural Monuments at the Pontifical Xavierian University of Bogotá. This text presents some of the findings achieved then and renovated with updated and relevant information of the two farmhouses and a rural village, located in the Department of Caldas, Colombia. The three objects of study are included in order to analyze and assess the agro-industrial heritage of the coffee zone; the house as a productive unit and the culture associated with it as a living heritage. Although, the initial purpose was to identify knowledge, skills, the memory of work, architecture and industrial landscape as elements of cultural heritage in that territory at different levels of traditional coffee growing. In this article, only the corresponding analysis of the farmhouse in the area estudied, is reflected. Therefore, it discusses, firstly, the notions of industrial heritage, the methodology used, and then addresses the physical characteristics of the coffee farmhouse, its heritage values and the possible threats currently facing the agro-industrial heritage in the country’s coffee zone.